PEMANFAATAN TANAMAN KANGKUNG DAN SAMPAH LINGKUNGAN SEBAGAI UPAYA PENINGKATAN EKONOMI MASYARAKAT DESA NGUMPAKDALEM DI MASA PANDEMI COVID 19 - Alif Yuanita Kartini (Mafaza : Jurnal Pengabdian Masyarakat, 2022)
Water spinach is commonly found around the community of Ngumpakdalem Village. Most people do not know the benefits and uses of kale. In addition, in Ngumpakdalem Village, a lot of plastic waste such as used drinking water bottles and even steroform were found. Of course this will interfere with environmental health if the people of Ngumpakdalem Village have not been able to manage waste properly. Therefore, in community service activities in Ngumpakdalem Village in collaboration with partners, in this case IDFoS Indonesia, Dalem Mandiri Sejahtera Group, Mandiri Sehat Group 1 and Mandiri healthy Group 2, held training on environmental waste management both organic and inorganic as organic fertilizer and media. environmentally friendly planting for kale plants. In this community service activity, the Asset Based Community Development (ABCD) method is used, which is a community development concept based on local assets to overcome problems in the area. The results of this community service activity are in the form of